Renewable Water Harvesting by Amyloid Aerogels and Sun. (7th October 2021) - Peydayesh, Mohammad; Greber, Tiara; Haechler, Iwan; Armanious, Antonius; Jia, Xiangze; Usuelli, Mattia; Bagnani, Massimo; Mezzenga, Raffaele
Abstract: Solar distillation is an appealing and facile technology for seawater desalination and water purification, but constructing stable, environmentally‐friendly, and cost‐effective solar evaporators often remain unfeasible. Here, amyloid hybrid aerogels are introduced for universal and renewable freshwater production by relying on the combination of sustainable materials and solar energy, thus making the process highly ecological and virtually costless. Amyloid fibrils obtained from whey, a byproduct of the dairy industry, are used as the main scaffold for the aerogels, whose solar energy harvesting properties of the top surface are enhanced by bioinspired dark polymers, such as polydopamine. Due to the fast water transport throughout the porous aerogels, the high‐yielding photothermal conversion ability of the top surface, and efficient heat insulation at the bottom, the hybrid amyloid fibrils aerogel exhibits a water evaporation rate of 1.61 kg·m −2 h −1 with a solar‐thermal conversion efficiency as high as 91.3% under 1 sun illumination. The process allows desalinating various seawater sources with different salinities to levels below the drinking water threshold recommended by the World Health Organization. Moreover, the same hybrid amyloid evaporator is highly efficient in removing heavy metals, organic pollutants, bacteria, and viruses from water, introducing a general, sustainable and energy‐efficient solution for desalination and water purification. Abstract : A novel solar evaporator for universal freshwater production composed primarily of amyloid fibrils obtained from whey, the main byproduct of the dairy industry, is introduced. By valorizing whey to fabricate a hybrid aerogel, two current global issues of supplying drinking water and waste management can simultaneously be tackled.